A clinical audit snapshot of Prostate Serum Antigen (PSA) test results for Pacific men from two Primary Health Care Clinics in the Auckland region, New Zealand - Nosa, Vili; Paynter, Janine; Heather, Maryann; Gentles , Dudley (Advances in Social Sciences Research Journal, 2022)
Prostate cancer is the most common malignancy registered in New Zealand and is the third most common cause of cancer death in men after lung cancer and bowel cancer. Prostate Serum Antigen (PSA) testing has been used to screen for prostate cancer. The following paper provides a clinical audit snapshot of Prostate Serum Antigen (PSA) test results for Pacific men from two Primary Health Care Clinics in the Auckland region, New Zealand. Two Auckland primary health care clinics provided anonymised data on prostate serum test results for their male patients along with ethnicity, age, and birthplace. Descriptive summaries of the data are presented as frequencies and percentages of positive test by age and by ethnic group. Logistic regression analysis was used to test for significant differences by ethnic group, age group and birthplace (NZ born versus overseas born). Two clinics which have predominately Pacific patients provided anonymised results of prostate serum antigen test results from 2009 – 2018. There were 5,787 prostate serum antigen level tests available from clinic 1 and clinic 2 had 493 patients. Most of the clinic patients tested were New Zealand born (5655, 90%) compared to overseas born (625, 10%). Samoans compared to Europeans were significantly more likely to have a positive test compared to Europeans & other ethnicities. Cook Island Maori men were significantly less likely to have a positive test result compared to European and other ethnicities. Older individuals are more likely to have positive PSA results which shows that this is very similar and consistent with the current literature. Those being born overseas compared to being New Zealand born were significantly less likely to have positive serum antigen results.